La cuestión nuclear iraní revisitada: tensiones, sanciones y negociaciones en torno al Plan de Acción Integral Conjunto de 2015 - Garduño García, Moisés (El Colegio de México, 2019)
The central argument of this paper defends the view that the Iranian nuclear issue must be studied as a geopolitical phenomenon. Although the nuclear deal was welcomed by the international community, the arrival of the Trump administration caused a return to a dynamic of conflict and mistrust. Washington’s withdrawal from the nuclear deal marks the beginning of the “maximum pressure strategy” to weaken Tehran in specific theaters such as Syria, Yemen, Iraq, and Lebanon, which includes a narrative of Islamophobia and Iranophobia in the transnational public sphere. From a historical perspective, this text examines some costs of sanctions for Iran, the unfeasibility of a military intervention during the first decade of the 21st century, and the strategic approach of Israel and Saudi Arabia during the Trump presidency, all in order to offer insights into the challenges facing the nuclear deal through spiraling cycles of tensions, sanctions, and negotiations